EFFECT OF DENTURE BASE MATERIALS IMMERSION IN NATURAL AND ARTIFICIAL SALIVA - Alexandru-Titus Farcașiu; Oana-Cella Andrei; Mihaela Păuna; Cătălina Farcașiu (Romanian Society of Oral Rehabilitation, 2015)
Aim of the study Evaluation of superficial adsorption of the glycoprotein layer on different denture base materials immersed in natural/artificial saliva. Material and methods Six denture base materials were investigated regarding wettability change following immersion in natural and artificial saliva. Contact angle measurements were carried out for the evaluation of wettability. Testing liquid was natural saliva for a more appropriate reproduction of the biological phenomenon. Results Both salivas improve the wettability of the substrates. Artificial saliva had an almost uniform effect on all materials. Natural saliva improved wettability with slight variations depending on the substrate and duration of immersion. Conclusions An increased wettability associated with the perfect fit principle and the maximum physiological extension of the denture base provide a better retention of the dentures. Artificial saliva should represent a mandatory part of the prosthetic treatment in xerostomic patients